2020
DOI: 10.1007/s10664-019-09783-w
|View full text |Cite
|
Sign up to set email alerts
|

Building the perfect game – an empirical study of game modifications

Abstract: Prior work has shown that gamer loyalty is important for the sales of a developer's future games. Therefore, it is important for game developers to increase the longevity of their games. However, game developers cannot always meet the growing and changing needs of the gaming community, due to the often already overloaded schedules of developers. So-called modders can potentially assist game developers with addressing gamers' needs. Modders are enthusiasts who provide modifications or completely new content for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 47 publications
0
21
0
2
Order By: Relevance
“…In extreme cases, the modder removes almost the entire original content of the game and creates a completely new one. This action is known as 'total conversion modding' [38,39].…”
Section: Game Modding As a Form Of Customers' Value Co-creationmentioning
confidence: 99%
“…In extreme cases, the modder removes almost the entire original content of the game and creates a completely new one. This action is known as 'total conversion modding' [38,39].…”
Section: Game Modding As a Form Of Customers' Value Co-creationmentioning
confidence: 99%
“…Modding occurs more often in single-player games than multiplayer, possibly because game producers wish to safeguard the gaming experience of their paying customers and take greater steps to prevent modding in games where it would affect players other than the modder (Lee et al, 2020). Regardless of the motivation to mod, whether game expansion or alteration, cheating or griefing, many consider modding multiplayer games to be of benefit to nobody (Kretschmar and Stanfill, 2019).…”
Section: Main Theme 4: Modding In Self-defencementioning
confidence: 99%
“…Modding can be defined as the act of editing an existing video game or gaming console to change elements or produce new material and capabilities and, thus, presents great diversity in potential modifications (e.g. Lee, Lin, Bezemer & Hassan, 2020). Modifications can be benevolent, such as fixing bugs, changing environments, producing game content (such as new maps), avatar skins and creative changes to the game itself.…”
mentioning
confidence: 99%
“…Several prior studies studied the modding community to identify and analyze the relationship between mod developers and the game industry, yielding insights on collaborative practices and strategies, as well as capturing the value of mods (Arakji and Lang 2007;Jeppesen 2004;Nieborg and Van der Graaf 2008). A few prior studies mined data from the Nexus Mods distribution platform to quantitatively study the motivation behind mod developers based on the users' expectations, and to understand how to build and maintain an active modding community (Dey et al 2016;Lee et al 2018). Particularly, Dey et al (2016) study the meta data available for popular and unpopular mods of six famous PC games across several popular online mod distribution platforms to investigate the motivations of mod developers.…”
Section: Empirical Studies Of Game Modsmentioning
confidence: 99%
“…There are two key components of an active modding community of a game: the active development of mods, and the active adoption of mods by gamers. In our prior work, we looked at how game developers can help maintain the active development of mods, and observed that games from developers with a consistent modding support within the same or different game franchises, were associated with faster releases of mods (Lee et al 2018). In this paper, we identify the characteristics that distinguish popular mods from unpopular ones.…”
Section: Introductionmentioning
confidence: 99%